GS/MS analysis and the antioxidant and antimicrobial properties of Salvia potentillifolia (Boiss. & Heldr.) ex Bentham - Albayrak, Sevil; Aksoy, Ahmet; Koyuncu, Songul (Istanbul Univ, Fac Pharmacy, 2024)
Background and Aims: Sage is traditionally used as an herbal tea in T & uuml;rkiye. In this study, the phenolic composition and biological potential of Salvia potentillifolia (Boiss. et Heldr.) ex Bentham (Lamiaceae) were determined. Methods: The essential oil constituents of S. potentillifolia were determined using gas chromatography/mass spectrometry (GC/MS). The in vitro antioxidant properties of the methanol extract of S. potentillifolia were tested spectrophotometrically using phosphomolybdenum assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, hydrogen peroxide (H2O2) scavenging, 3-carotene bleaching inhibition, Fe2+ chelating, reducing power, ferric ions reducing activity (FRAP), and cupric ion reducing activity (CUPRAC) assays. The total phenolic and flavonoid contents of the methanol extract were determined. The antimicrobial effects of the methanol extract and essential oil were detected against 12 bacteria, 1 yeast, and 2 aflatoxigenic fungi strains using agar-well diffusion and the micro-well dilution methods. Results: Fifty compounds were detected in the essential oil. The major oil component was eucalyptol. It was followed by carvacrol, 3-pinene, borneol, camphor, alpha-terpineol, 4-terpineol, bornyl acetate, and caryophyllene. The methanol extract of S. potentillifolia had effective DPPH radical scavenging, Fe3+ reducing, and Cu2+ reducing activities while exerting weak H2O2 scavenging and Fe2+ chelating activities. The methanol extract had weak antibacterial activity, whereas the essential oil had moderate antibacterial activity. The methanol extract had no antifungal potency against the tested aflatoxigenic fungi. Conclusion: The methanol extract of S. potentillifolia is a natural antioxidant resource, whereas the essential oil may be a natural antibacterial agent. It is believed that the results of this study will contribute to the recently increasing research on the use of natural antioxidant and antimicrobial compounds as an alternative to synthetic compounds in various industrial fields, such as food, pharmacy, and medicine.
Keywords: Antimicrobial; Antioxidant; Essential oil; Salvia potentillifolia